A renúncia a arte: a norma contemporânea e sua influência na prática médica pós-moderna - Ricardo de Menezes Macedo (2009)
The principles of the medicine are noble and of great value for the doctors and the society. They are described in the literature of some forms, we can to summarize them as: the priority of well-being of the patient, the beginning of the autonomy of the patient and social justice. To reach them, of them if they unfold the relation doctor-patient, the medical art, the ethics, solidarity, science. However, these are professionals who today take offense themselves at great dissatisfaction in its work. It has an apparent contradiction in the agreement of this phenomenon. This thesis has as objective the paper or effect of these principles in the world contemporary, as well as, to evaluate if they are capable, ahead of high modernity, to alleviate the malaise that the doctors feel in relation to its profession. The apparent contradiction enters the beddings of modernity - as reason the scientific and economic technician/- and the principles of the medicine was the object of this study. The used method was a Theoretical Assay. One concludes that the principles of the medicine are in the opposite direction of high modernity, but the doctors, in contrast are with it identified. The contemporaries’ principles are in function of a Homo œconomicus that normalizes the individual overshadows it the citizen. Thus, the doctor, in the security guard search, abdicates of its art, dangerous place and replete of uncertainties. The principles of the medicine, in stimulating to the one the moral and solidary position, suffer transformations in the high structure from the society, and finish in returning from modified form, reflexivity, operating with efficiency the control mechanisms it time. Of this form, when forcing the doctor to the restriction of the contact with the sick person, compels them to modernity to appealing to the technique; not only for its instrumental function, but to alleviate its anxiety. As result, the priority of the sick person if transmute in wild consumption; this yes an icon of our time.